PENGEMBANGAN LEMBAR KEGIATAN SISWA BERBASIS KEARIFAN LOKAL TEMA KEGEMARANKU SUBTEMA GEMAR BEROLAHRAGA & GEMAR BERNYANYI DAN MENARI DI KELAS I SDN UTAMA 1 TARAKAN - Tiara Adi Pratiwi (Universitas PGRI Madiun, 2016)
This research aims to produce students’ worksheet based on local wisdom for first grade on theme my hobbies subtheme love in doing sports& singing and dancing of SDN Utama 1 Tarakan. This research was Research and Development with adopt procedure from Borg and Gall which is potential and problem, gather information, product design, design validation, the revised design, product testing, product revision, testing usage, and product revision. This result showed that : (a) student worksheet included in the category of valid from aspect content and material with average score 4,44 category very good, aspect language with average score 4 category good, and aspect desain with average score 4,04 category very good (b) student worksheet included in the category of practic with average score 3,83 category good (c) student worksheet included in the category effective from aspect observation student activity with average score 3,45 category good, aspect student respons with average score 4,32 category very good, and aspect of students learning outcomes with average score 4,74 category very good. Keyword: Student Worksheet, Local Culture